Penyajian Akuntansi Qardhul Hasan Dalam Laporan Keuangan Perbankan Syariah - Ana Kadarningsih (Universitas Alma Ata, 2017)
The rise of the establishment of Islamic Banks and the opening branch of conventional banks that provide services using sharia system (office channeling) have increase financial transactions in Islamic Laws indirectly. Qardhul hasan is one of the most important financial transactions in Islamic Laws. The public do not have enough comprehension about qardhul hasan. Therefore, this study aims to explain the process of preparing accounting for qardhul hasan in Islamic Banks . This accounting process will establish financial statements for Islamic Banks based on standard juridical (or law's regulations) and normative (al-Qur'an and Sunnah) . The results of literature review show accounting process for qardhul hasan in Islamic Banks must be implemented with existing regulations so it can be used by stakeholders as a form of transparency (tabligh), validiy (shidiq) of financial report, professionalism (fathonah) and accountability (amanah) for Islamic Banks.